Glass Ceiling over Private Equity - Stefanovic, Nikola; Makojevic, Nikola; Stanisic, Nemanja (Industrija, 2014)
The study investigated the glass ceiling in private equity companies in emerging markets. The research covered 119 private equity companies, members of the Emerging Markets Private Equity Association. The companies employed 736 top executives, in forty-two countries. The results showed that women occupied sixty-six top executive positions, representing 8.97 percent. The results also showed statistically significant differences in the average values of the percentage of women occupying the top executive positions, depending on the geographic location of the companies. The geographic distribution of the average values showed a significant correlation with the economic development levels and the Hofstede cultural dimensions.